2021
DOI: 10.3390/biomedicines9050486
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating Lymphocytes in the Tumor Microenvironment of Laryngeal Squamous Cell Carcinoma: Systematic Review and Meta-Analysis

Abstract: The presence of tumor-infiltrating lymphocytes (TIL) in the tumor microenvironment has been demonstrated to be of prognostic value in various cancers. In this systematic review and meta-analysis, we investigated the prognostic value of TIL in laryngeal squamous cell carcinoma (LSCC). We performed a systematic search in PubMed for publications that investigated the prognostic value of TIL in LSCC. A meta-analysis was performed including all studies assessing the association between TIL counts in hematoxylin-eos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 50 publications
(140 reference statements)
3
31
1
Order By: Relevance
“…17 Previous studies showed a prognostic favorable role for several subtypes of tumor-infiltrating T cells, especially CD4 and CD8. 5,6,18 In our study, higher expression of CD4 + and CD8 + TILs were significant prognostic factors with positive impact on both OS and DSS in univariate analysis, but not in multivariate analysis. High tumoral and peritumoral density of CD4 and CD8 was identified as a positive predictor of OS, DSS, and disease free survival (DFS) in other studies as well.…”
Section: Discussionmentioning
confidence: 46%
“…17 Previous studies showed a prognostic favorable role for several subtypes of tumor-infiltrating T cells, especially CD4 and CD8. 5,6,18 In our study, higher expression of CD4 + and CD8 + TILs were significant prognostic factors with positive impact on both OS and DSS in univariate analysis, but not in multivariate analysis. High tumoral and peritumoral density of CD4 and CD8 was identified as a positive predictor of OS, DSS, and disease free survival (DFS) in other studies as well.…”
Section: Discussionmentioning
confidence: 46%
“…TME is a complex ecosystem and an active participant in all stages of LSCC occurrence and development [20]. TME is composed of many cell types, which can regulate too many cell-cell interactions, further playing a significant impact on cancer development, progression, and treatment [21].…”
Section: Discussionmentioning
confidence: 99%
“…TME is a complex ecosystem and an active participant in all stages of LSCC occurrence and development [ 20 ]. TME is composed of many cell types, which can regulate too many cell-cell interactions, further playing a significant impact on cancer development, progression, and treatment [ 21 ]. As one cell type with abundant stromal in TME, macrophages are highly plastic and can be activated into M1 or M2 polarization by stimulation of different chemokines and cytokines from TME [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…TILs are considered the most crucial effectors to protect against tumor development in the TME [87]. Importantly, several studies have recognized TILs as an important biomarker and a favorable prognostic factor for treatment and clinical outcomes of HNSCC [88,89]. The major components of TILs are T lymphocytes, including cytotoxic T lymphocytes (CD8+ T cells), and helper T lymphocytes (CD4+ T cells), which play a role in tumor elimination [90,91].…”
Section: Exosomal Mirnas Crosstalk Between Hnscc and Tilsmentioning
confidence: 99%